A ten-faced hexangulaconulariid from Cambrian Stage 2 of South China. (September 2021) - Guo, Junfeng; Han, Jian; Van Iten, Heyo; Song, Zuchen; Qiang, Yaqin; Wang, Wenzhe; Zhang, Zhifei; Li, Guoxiang
Abstract: Hexangulaconulariids (Cambrian stages 1–2) are an extinct group of medusozoan polyps having a biradially symmetrical, fan-shaped periderm that is distinct from those of medusozoan polyps showing three-, four-, five-, or six-fold radial symmetry. Hexangulaconulariids exhibit substantial variation in gross morphology, including variation in the number of faces on each of the two major sides of the periderm. An intermediate taxon of hexangulaconulariids with ten faces (five on each major side) was expected. Here we describe a new hexangulaconulariid, Decimoconularia isofacialis new genus new species from Bed 5 of the Yanjiahe Formation (Cambrian Stage 2) in the Three Gorges area of Hubei Province, China. The new taxon differs from other hexangulaconulariids ( Arthrochites, Hexaconularia, and Septuconularia ) mainly in possessing a total of ten faces. The two lateral margins are each marked by a ridge in about the apertural half of the periderm and by a collinear furrow in about the apical half, while the five faces on each major side are bounded by a furrow in about the apertural half and by a collinear ridge in about the apical half. Among hexangulaconulariids, Decimoconularia and Septuconularia may be more closely related to each other than either genus is to Arthrochites or Hexaconularia . UUID: http://zoobank.org/ca270a3b-25ee-4d1f-bdeb-91a963370e70